The Role of Digital Literacy in Improving Employee Performance at the Agriculture Office of Banten Province - Nurmeryteni, Indriyan; Stiawati, Titi; Rifai, Mohamad Arief; Kusumawati, Destri (Indonesian Journal of Social Science Research, 2026)
Digital transformation in the public sector requires employees with adequate digital literacy. However, a digital skills gap persists, particularly in local government agencies such as the Banten Provincial Agriculture Office. This study aims to examine the role of digital literacy in improving employee performance using a literature review approach. Data were obtained from various recent national and international publications (2020–2025), sourced from journals, books, and other relevant scientific references. Therefore, this study will produce a study model that shows that digital literacy contributes significantly to improving employee performance, particularly in improving work efficiency, the quality of data-based decision-making, and strengthening technological competency through service innovation at the Banten Provincial Agriculture Office. Therefore, the implementation of digital literacy is a key factor that needs to be prioritized strategically in efforts to improve employee performance while supporting the public sector's transformation towards a sustainable digital agricultural system.